Die loopbaanbelewenis van akademici aan Suid-Afrikaanse universiteite: CAP ondersoek - Charl Wolhuter; Corene de Wet; Philip Higgs; Leonie Higgs; Isaac Ntshoe (Acta Academica, 2010)
This article aims to explain how South African academics experience their professional lives during different career phases by employing data from the international Changing Academic Profession (CAP) investigation into the academic profession. Two perturbing aspects emanate from the research. First, how academics during the early career phase (ages 20-39 years) experience being constricted, in view of their roles as researchers and the fact that this phase is typically the most creative in one’s career. Similarly, the fact that academics in the mid-career phase (ages 40-55 years) show the lowest levels of job satisfaction is a cause for concern, as these years are typically the most productive in one’s career.